Microtomographic Analysis of Lower Urinary Tract Obstruction. (November 2013) - Siebert, Joseph R.; Smith, Kenneth J.; Cox, Liza L.; Glass, Ian A.; Cox, Timothy C.
Prenatal obstruction of the lower urinary tract may result in megacystis, with subsequent development of hydroureter, hydronephrosis, and renal damage. Oligo- or anhydramnios, pulmonary hypoplasia, and prune belly syndrome are lethal consequences. Causes and mechanisms responsible for obstruction remain unclear but might be clarified by anatomic study at autopsy. To this end, we employed 2 methods of tomographic imaging—optical projection tomography and contrast-enhanced microCT scanning—to elucidate the anatomy of the intact urinary bladder and urethra in 10 male fetuses with lower urinary tract obstruction. Images were compared with those from 9 age-matched controls. Three-dimensional images, rotated and sectioned digitally in multiple planes, permitted thorough examination while preserving specimens for later study. Both external and internal features of the bladder and urethra were demonstrated; small structures (ie, urethral crest, verumontanum, prostatic utricle, ejaculatory ducts) were seen in detail. Types of obstruction consisted of urethral atresia ( n = 5), severe urethral stenosis ( n = 2), urethral diaphragm ( n = 2), or physical kinking ( n = 1); classic (Young type I) posterior urethral valves were not encountered. Traditional light microscopy was then used to verify tomographic findings. The prostate gland was hypoplastic or absent in all cases; in 1, prostatic tissue was displaced inferior to the verumontanum. Findings support previous views that dissection may produce valve-like artifacts (eg, bisection of an obstructing diaphragm) and that deformation of an otherwise normal urethra may result in megacystis. The designation "posterior urethral valves" should not be used as a generic expression of urethral obstruction unless actual valves are demonstrated.